A charged particle veto detector for kaonic deuterium measurements at DAΦNE. (November 2018) - Tüchler, M; Zmeskal, J; Amirkhani, A; Bazzi, M; Bellotti, G; Berucci, C; Bosnar, D; Bragadireanu, A M; Cargnelli, M; Curceanu, C; Dawood Butt, A; Del Grande, R; et al.
Abstract: The antikaon-nucleon interaction close to threshold provides crucial information on the interplay between spontaneous and explicit chiral symmetry breaking in low-energy QCD. In this context, the importance of kaonic deuterium x-ray spectroscopy has been well recognized, but no experimental results have yet been obtained due to the difficulty of the measurement. To measure the shift and width of the kaonic deuterium 1s state with an accuracy of 30 eV and 75 eV, respectively, an apparatus is under construction at the Laboratori Nazionali di Frascati. A detailed Monte Carlo simulation has shown that an increase of the signal to background ratio by a factor of ten will be required compared to the successfully performed kaonic hydrogen measurement (SIDDHARTA). Three pillars are essential for the newly developed experimental apparatus: a large area x-ray detector system (consisting of Silicon Drift Detectors), a lightweight cryogenic target system and a veto system, consisting of an outer veto detector (Veto-1) for active shielding and an inner veto detector (Veto-2) for charged particle suppression. For both veto systems, an excellent time resolution is required to distinguish kaons stopping in gas from direct kaon stops in the entrance window or side wall of the target. First test measurements on the Veto-2 system were performed. An average time resolution of (54 ± 2) ps and detection efficiencies of ~ 99 % were achieved.